Komunikasi Interpersonal Komunitas Pelita dalam Membangun Toleransi Beragama - Riyadi, Agus; Wigati, Yunika Indah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This article discusses religious tolerance in the perspective of interpersonal communication. This research was conducted using descriptive qualitative methods through a phenomenological approach. The results showed that inter-personal communication patterns that occurred between members of the Pelita community in building religious tole-rance based on interpersonal competence, friendship asso-ciations, professional relationships, and websites for inter-personal relationships. While romantic communication pat-terns and family relationships did not appear. This is because Pelita was medium for people meeting from various religious backgrounds who were not tied based on genetic, but com-munication amongst members relying on the social and national based relationship.